2015
DOI: 10.1309/lmn1p2frz7bkzsco
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Hemorrhagic Fever

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is a member of the Bunyaviridae family and Nairovirus genus. The viral genome consists of 3 RNA segments of 12 kb (L), 6.8 kb (M), and 3 kb (S). Crimean-Congo hemorrhagic fever (CCHF) is the most widespread tickborne viral infection worldwide: it has been reported in many regions of Africa, the Middle East, and Asia. The geographical distribution of CCHFV corresponds most closely with the distribution of members of the tick genera, and Hyalomma ticks are the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 94 publications
2
102
0
2
Order By: Relevance
“…Smaller sporadic outbreaks of Far-eastern subtype tick-borne flavivirus, RVFV, and CCHFV occur on a yearly basis and have previously been reported in Siberia/Russia, Africa/Arabian Peninsula, and Southeastern Europe, respectively333435. The mortality rate can reach up to 20 and 50% for respectively RSSEV and CCHFV3637, while RVFV rather causes a permanent debilitating disease in about 10% of cases38. Currently there is no specific antiviral treatment or vaccine for EBOV, as well as for other highly pathogenic viruses such as RSSEV, CCHFV, and RVFV3940, therefore there is an urgent need for the development of broad-range safe and effective antiviral therapeutics.…”
Section: Discussionmentioning
confidence: 89%
“…Smaller sporadic outbreaks of Far-eastern subtype tick-borne flavivirus, RVFV, and CCHFV occur on a yearly basis and have previously been reported in Siberia/Russia, Africa/Arabian Peninsula, and Southeastern Europe, respectively333435. The mortality rate can reach up to 20 and 50% for respectively RSSEV and CCHFV3637, while RVFV rather causes a permanent debilitating disease in about 10% of cases38. Currently there is no specific antiviral treatment or vaccine for EBOV, as well as for other highly pathogenic viruses such as RSSEV, CCHFV, and RVFV3940, therefore there is an urgent need for the development of broad-range safe and effective antiviral therapeutics.…”
Section: Discussionmentioning
confidence: 89%
“…Crimean-Congo Haemorrhagic Fever Virus (CCHFV) is a single-stranded RNA virus with three segments (large, medium, and small), two envelope proteins (Gn and Gc) and an RNA-dependent RNA polymerase [1][2][3]. Studies have found the GC protein to be the target-binding protein as well as an important mediator for virus entry [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incubation period varies depending on how infection occurs. It can last up to 9 days when the disease is acquired through a tick bite and a maximum of 13 days when transmission occurs by infected tissues or blood [3]. Next, the pre-haemorrhagic period involves a broad-albeit non-specific range of symptoms such as fever, chills, severe headache, photophobia, myalgia, abdominal pain, nausea, flushing, hypotension, and bradycardia [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crimean-Congo hemorrhagic fever virus (CCHFV) is an enveloped RNA virus, which is classified in Nairovirus genus, Bunyaviridae family (1). The virus is distributed throughout more than 30 countries in Africa, Asia, southeast Europe, and the Middle East including Iran (2).…”
Section: Introductionmentioning
confidence: 99%